2019
DOI: 10.1177/0391398819868481
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized equine carotid artery layers as matrix for regenerated neurites of spiral ganglion neurons

Abstract: Today’s best solution in compensating for sensorineural hearing loss is the cochlear implant, which electrically stimulates the spiral ganglion neurons in the inner ear. An optimum hearing impression is not ensured due to, among other reasons, a remaining anatomical gap between the spiral ganglion neurons and the implant electrodes. The gap could be bridged via pharmacologically triggered neurite growth toward the electrodes if biomaterials for neurite guidance could be provided. For this, we investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(98 reference statements)
0
7
0
Order By: Relevance
“… Xie et al (2012) showed that a BDNF reservoir leads to a long distance axonal growth of hippocampal neurons along an ordered channel system. Further studies support the successful guidance of SGNs along ordered structures and their positive effect on the length of the neurites ( Leigh et al, 2017 ; Yilmaz-Bayraktar et al, 2020 ). Whereas other studies have reported a neuroregenerative effect of BDNF, based on increasing lengths of neurites ( Gao et al, 2016 ; McGregor and English, 2019 ), we were not able to confirm this in the present work nor in former BDNF delivery experiments ( Schmidt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“… Xie et al (2012) showed that a BDNF reservoir leads to a long distance axonal growth of hippocampal neurons along an ordered channel system. Further studies support the successful guidance of SGNs along ordered structures and their positive effect on the length of the neurites ( Leigh et al, 2017 ; Yilmaz-Bayraktar et al, 2020 ). Whereas other studies have reported a neuroregenerative effect of BDNF, based on increasing lengths of neurites ( Gao et al, 2016 ; McGregor and English, 2019 ), we were not able to confirm this in the present work nor in former BDNF delivery experiments ( Schmidt et al, 2018 ).…”
Section: Discussionmentioning
confidence: 68%
“…Even though not investigated in this study, a BDNF concentration gradient emanating from the polymer fibers could be a conceivable method for not only enhancing the survival rate of the SGNs, but also for guiding their neurites along the fibers and finally towards the surface of the implant. Several studies have demonstrated neuronal growth towards a neurotrophin concentration gradient ( Xie et al, 2012 ; Li H. et al, 2017 ; Yilmaz-Bayraktar et al, 2020 ). Xie et al (2012) showed that a BDNF reservoir leads to a long distance axonal growth of hippocampal neurons along an ordered channel system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been reported that decellularized equine carotid arteries showed positive effects on neurite regeneration. 29 However, the disadvantage is that these materials are less stable and homogeneous, may also damage electrodes and increase current diffusion. Some studies have also attempted to use cochlear electrode coatings as a drug delivery system, for example by adding drugs such as dexamethasone for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%